Konsepsi Masyarakat Adat dan Problematika Pengakuan dan Perlindungannya - M. Hatta Roma Tampubolon (Fakultas Hukum Universitas Mulawarman, 2010)
The oppressive treatment against indigenous peoples has been occurred already in some aspects such as economic, politic, law, and social and cultural. It becomes ironic because in fact, the indigenous peoples is the largest element for nation-state structure of Indonesia. However, almost in all national politic decisions, the existence of custom communities is not accommodated, or systematically, isolated from the political process or national politic agenda. Considering the product reality of the state law, it is admitted that national politic elites have two faces. They modernize the law but still adore the charm of custom law. The national law already gives a chance for the indigenous peoples and their custom law to be developed in the legislation context. However, this chance is not seriously given because of the assumption that custom law is only decelerating the national progress.